Acupuncture for retinitis pigmentosa: study protocol for a randomised, sham-controlled trial - Jing Wang; Na Gao; Hui Huang; Haoran Li; Ruxue Lei; Weiwen Zou; Qun Huang; Yanlin Zheng (BMJ Open, 2021)
Introduction Primary retinitis pigmentosa (RP) is a common hereditary retinal disease in ophthalmology that has a considerable impact on quality of life, but there are few effective therapeutic strategies. This trial aims to determine the efficacy and safety of acupuncture versus sham acupuncture (SA) for RP.Methods and analysis This is a study protocol for a randomised, participant-blind, sham-controlled trial. 64 eligible patients with RP will randomly be divided into acupuncture group and SA group. All groups will receive 48 sessions over 3 months. Participants will complete the trial by visiting the research centre in month 6/9 for a follow-up assessment. The primary outcome is visual field mean sensitivity and visual field mean deviation at month 3/6/9 compared with baseline. Secondary outcomes include the best-corrected visual acuity, central macular thickness, subfoveal choroidal thicknes, traditional Chinese medicine syndrome score and the scale of life quality for diseases with visual impairment at month 3/6/9 compared with baseline. Adverse events and safety indexes will be recorded throughout the study. SPSS V.25.0 statistical software was used for analysis, and measurement data were expressed as mean±SD.Ethics and dissemination Ethics approval was obtained from the Ethics Committee of the Chinese Clinical Trial Registry (approval no: ChiECRCT20200460). The results of this study will be published in a peer-reviewed journal, and trial participants will be informed via email and/or phone calls.Trial registration number ChiCTR2000041090.